1999
DOI: 10.1099/00222615-48-1-17
|View full text |Cite
|
Sign up to set email alerts
|

DNA typing of methicillin-resistant Staphylococcus aureus: isolates and factors associated with nosocomial acquisition in two Brazilian university hospitals

Abstract: Control and prevention of methicillin-resistant staphylococcus aureus (MRSA) infections should include early identification of patients at higher risk of MRSA acquisition and analysis of isolates by discriminatory bacterial DNA typing methods. One hundred and three MRSA isolates cultured between Sept. 1994 and Sept. 1995 from 62 patients in two teaching hospitals (hospital 1, in Rio de Janeiro; hospital 2, in Minas Gerais) were tested for antimicrobial resistance and genomic DNA was analysed by pulsed-field ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
49
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(56 citation statements)
references
References 26 publications
7
49
0
Order By: Relevance
“…While antimicrobial susceptibility testing is routinely performed by clinical microbiology laboratories on most bacterial isolates to aid in the identification of new or unusual patterns of antibiotic resistance, the results can only raise the suspicion of an outbreak or the presence of a new strain. This is due to the fact that antibiotic susceptibility testing has relatively limited use in epidemiological studies because of phenotypic variation as observed in this study, and because antibiotic resistance is affected by selective pressure in hospitals [10]. Therefore strain typing provides a more robust epidemiological tool for MRSA infection in the population.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…While antimicrobial susceptibility testing is routinely performed by clinical microbiology laboratories on most bacterial isolates to aid in the identification of new or unusual patterns of antibiotic resistance, the results can only raise the suspicion of an outbreak or the presence of a new strain. This is due to the fact that antibiotic susceptibility testing has relatively limited use in epidemiological studies because of phenotypic variation as observed in this study, and because antibiotic resistance is affected by selective pressure in hospitals [10]. Therefore strain typing provides a more robust epidemiological tool for MRSA infection in the population.…”
Section: Discussionmentioning
confidence: 96%
“…The acquisition of MRSA has many risk factors associated included prolonged hospitalisation, preceding antimicrobial therapy, use of invasive procedures, treatment in an intensive care unit, surgical procedures and close proximity to a patient colonised or infected with MRSA [4,6,10]. Furthermore, heavy dependency, i.e., patients requiring considerable nursing and other support is another risk factor that should be considered [10].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The experiments were performed in triplicate and classified according to Stepanovic et al, 2007. The primers used were: mecA MRS1 (5' TAGAAATGACTGAACGTCCG 3') and MRS2 (5' TTGCGATCAATGTTACCGTAG 3') (Santos et al, 1999); icaA Forward (5' CGATGGGCTCAAGGTGG 3') and icaA Reverse (5' TTCTTTTCGTAGCGACTGTC 3') for the gene icaA, and bap2 Forward (5' GAGCCAGATAAACAACAAGAAG 3') and bap2 Reverse (5' CATGCTCAGCAATAATTGGATC 3') (Potter et al, 2009 (5'GAGTTTGATCCTGGCTCAG 3') and 1492r (5'…”
Section: Methodsmentioning
confidence: 99%